2004
DOI: 10.2337/diabetes.53.10.2617
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Insulin Resistance Precedes the Development of Diabetes in a Model of Intrauterine Growth Retardation

Abstract: Intrauterine growth retardation (IUGR) has been linked to the development of type 2 diabetes in adulthood. We developed an IUGR model in rats whereby at age 3-6 months the animals develop a diabetes that is associated with insulin resistance. Hyperinsulinemiceuglycemic clamp studies were performed at age 8 weeks, before the onset of obesity and diabetes. Basal hepatic glucose production (HGP) was significantly higher in IUGR than in control rats (14.6 ؎ 0.4 vs. 12.3 ؎ 0.3 mg ⅐ kg ؊1 ⅐ min ؊1 ; P < 0.05). Insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 56 publications
9
103
3
Order By: Relevance
“…Barker (1993) suggested that low birth weight was associated with increased risk of metabolic syndrome in adulthood. The restriction of dietary protein or a global restriction in nutrients during pregnancy gives rise to the offspring with glucose intolerance and insulin resistance (Langley et al 1994, Vuguin et al 2004, which supports the above concept. Insulin resistance is recognized as a common underlying feature of metabolic syndrome, but the mechanisms at the cellular and biochemical levels are not completely understood.…”
Section: Ghrelin Expression In Pancreatic Isletssupporting
confidence: 64%
“…Barker (1993) suggested that low birth weight was associated with increased risk of metabolic syndrome in adulthood. The restriction of dietary protein or a global restriction in nutrients during pregnancy gives rise to the offspring with glucose intolerance and insulin resistance (Langley et al 1994, Vuguin et al 2004, which supports the above concept. Insulin resistance is recognized as a common underlying feature of metabolic syndrome, but the mechanisms at the cellular and biochemical levels are not completely understood.…”
Section: Ghrelin Expression In Pancreatic Isletssupporting
confidence: 64%
“…Despite a similar basal glucose turnover in young twins and singletons, we demonstrated a negative association between basal glucose turnover and PI in both young twins and singletons. Vuguin et al (31) reported an elevated basal hepatic glucose production in normoglycemic intrauterine growth-retarded rats compared with control rats, indicating that uteroplacental insufficiency causes a primary defect in hepatic metabolism before the onset of overt hyperglycemia. Another study in animals demonstrated that an adverse intrauterine environment induced by dexamethasone resulted in overexpression of hepatic PEPCK and increased gluconeogenesis (32).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic insulin resistance is characterized by a blunted suppression of hepatic glucose production in response to insulin, which is secondary to the impairment of insulin signaling (20). A postreceptor defect in the intracellular insulin signaling cascade decreases the insulin-induced suppression of hepatic glucose production (21).…”
Section: Articlesmentioning
confidence: 99%